Estudo do processo de soldagem por fricção por ponto da liga de magnésio AZ31 - Campanelli, Leonardo Contri (2012)
The great potential of magnesium alloys on reducing structural weight and therefore contributing with energy efficiency of transportation facilities has mainly attracted the automotive and aeronautic industries. The difficulty of joining such materials is one of the biggest challenges to overcome, expanding opportunities for solid state welding technologies. This work was carried out to study the feasibility of joining AZ31 magnesium alloy by friction spot welding (FSpW) process. The purpose was to evaluate the influence of the process parameters on microstructure and mechanical properties of the welded joints, as well as to comprehend the fracture behaviors of the welds under shear loading and to optimize the welding process. The joints were produced in overlap configuration through different combinations of parameters, which were established by statistical methods for design of experiments, and later submitted to mechanical and metallurgical characterization. For assessing the failure mechanisms, modeling and simulation of stress distribution around the weld during lap shear test were performed. The results confirmed the possibility of joining AZ31 alloy through FSpW, as well as the superiority when compared to friction stir spot welding (FSSW) process. Although the change on the tool profile had shown a significant effect over the process parameters and weld strength, the maximum load values demonstrated the robustness of the welding process. Microstructural regions exhibited an enhanced level of uniformity, with the exception of recrystallized zone. Mechanical behavior presented a strong dependence on metallurgical features arising from the flow of plasticized material, which were identified as bonding lines and hook, as well as the condition of material stirring. The flexural loading associated to the inaccurate alignment of the welded specimen emerged as an operational variable, also influencing the crack propagation path.